Prospecting the interaction interface in the polymerization process of the enzyme glutaminase C - Abreu, Flávia Mayumi Odahara de (2023)
The energetic and biosynthetic demands in cancer are linked to the alteration of many pathways in the cell. One of the main changes occurs in glutaminolysis; glutamine is one of the essential nutrients for tumor metabolism and is converted into glutamate by the glutaminase enzymes, encoded in mammals by two distinct genes, GLS and GLS2. Among the existing isoforms, Glutaminase C (GAC) is crucial and found in abundance in different tumor lineages. It can be found in different oligomeric states with varying efficiency, and the most active type is characterized by the formation of helical filaments (fGAC) in the presence of inorganic phosphate (Pi). However, the molecular mechanism by which oligomerization and increased activity arise is still elusive. Therefore, this project aims to discuss a novel model proposed by our group through the combination of cryo-electron microscopy (cryo-EM) and biochemical studies of the wild-type or modified protein. To this end, site-directed mutagenesis was performed in residues from regions of the suggested interaction interface and activation loop. Wildtype mouse GAC and its mutants were produced by heterologous expression in bacteria on a large scale in soluble fraction and purified in three stages. By dynamic light scattering (DLS) analysis, it was possible to observe a shift from the tetrameric to the filamentous form of the wild-type protein upon addition of Pi, while mutants remained in their initial state under the same conditions. Enzymatic efficiency was confirmed by kinetic assays based on a coupled reaction, tracking the absorbance of 340 nm wavelength light by NADH formed during the conversion of glutamate into α- ketoglutarate by the enzyme glutamate dehydrogenase (GDH). Analysis showed that the mutants also show reduced efficiency in contrast to the wild-type protein even in the presence of Pi. Thus, the data suggest that mutations that prevent filamentation are also responsible for inactivating the protein, confirming that substituted residues are critical for the formation, stabilization, and function of fGAC. We propose a mechanism for the transition from inactive dimers to hyper-active fGAC; understanding this process could establish the enzyme Glutaminase C as a promising molecular target for the development of new anti-tumor therapies.